Plant growth promoting rhizobacteria (PGPR): Biofertiliser and Biocontrol agent-Review article - Bajracharya, Anup Muni (Journal of Balkumari College, 2019)
Good health starts with good food. Humans expect agriculture to supply good food with sufficient nutrients, economically and culturally valued foods, fibers and other products. But the excessive application of synthetic pesticides has exerted an adverse effect on bio-flora, fauna and natural enemies. Even a largest part of yield has been lost due to various stresses, like biotic and abiotic stresses to the plant. On this account, plant growth promoting rhizobacteria (PGPR), an eco-friendly biopesticides is boon for the biocontrol of different plant pathogens. Moreover, PGPR strains can enhance the plant growth through the production of various plant growth promoting substances. These are generally a group of microorganism that is found either in the plane of the rhizosphere or above roots impacting some positive benefits to plants. PGPR are associated with plant roots and augment plant productivity and immunity; however, recent work by several groups shows that PGPR also elicit so-called 'induced systemic tolerance' to salt and drought. PGPR might also increase nutrient uptake from soils, thus reducing the need for fertilizers and preventing the accumulation of nitrates and phosphates in agricultural soils. Scientific researches involve multidisciplinary approaches to understand adaptation of PGPR, effects on plant physiology and growth, induced systemic resistance, biocontrol of plant pathogens, bio fertilization, and potential green alternative for plant productivity, viability of co inoculating, plant microorganism interactions, and mechanisms of root colonization.